Integrasi Nilai Akidah Akhlak dalam Pendidikan Karakter Islam Berbasis Literatur Ulama Klasik dan Kontemporer - M. Dimas Suhaimi Zein; Syaiful Bahri Tanjung; Muthi Nurhanifah; Indi Yusmardani; Muhammad Basri; Zulfahmi Lubis (E-Jurnal Aksioma Ad Diniyyah : The Indonesian Journal of Islamic Studies, 2025)
Character education is a fundamental aspect of the Islamic education system, aiming to shape the holistic and balanced personality of students. This article examines the integration of religious and moral values ​​in Islamic character education, based on classical and contemporary Islamic scholarly literature. This study uses a qualitative approach with library research methods, with the primary data sources being the works of classical scholars such as Al-Ghazali, Az-Zarnuji, and KH. Hasyim Asy'ari, as well as Islamic education books and national journal articles from the past five years. Data were analyzed using content analysis with normative-philosophical and historical-contextual approaches. The results of the study indicate that the integration of faith and moral values ​​is the core of Islamic character education. Classical scholars emphasize the development of faith, manners, role models, and habits as the main methods of character education, while contemporary thought highlights the importance of an integrative, holistic, and contextual approach in facing the challenges of modern education. This article formulates a model of integration of faith and moral values ​​in Islamic character education that includes four main pillars, namely faith as a source of values, morals as the goal of education, role models and habits as methods, and the educational environment as a moral ecosystem. This integration is expected to be able to shape the character of students who are faithful, have noble morals, and are adaptive to global dynamics without losing their Islamic identity